Association of bilateral flat feet with knee pain and disability in patients with knee osteoarthritis: A cross‐sectional study. Issue 11 (24th April 2017) - Iijima, Hirotaka; Ohi, Hiroshi; Isho, Takuya; Aoyama, Tomoki; Fukutani, Naoto; Kaneda, Eishi; Ohi, Kazuko; Abe, Kaoru; Kuroki, Hiroshi; Matsuda, Shuichi
ABSTRACT: This cross‐sectional study examined the relationship of flat feet with knee pain, disability, and physical performance in patients with knee osteoarthritis (OA). Orthopedic clinic participants ( n  = 95; age 61–91 years; 68.4% women) with Kellgren‐Lawrence (K/L) grade ≥1 in the medial compartment underwent evaluation of navicular height and foot length for flat feet. Knee pain intensity, disability, and physical performance were evaluated using the Japanese Knee Osteoarthritis Measure, 10‐m walk, timed up and go, and five‐repetition chair stand tests. Of the 95 enrolled patients, 24 (25.3%) had bilateral flat feet, and significantly higher knee pain compared to patients with no flat feet (11.3 ± 8.23 points vs. 6.58 ± 6.37 points; p  = 0.043). A ordinal logistic regression analysis showed that bilateral flat feet were significantly associated with increased knee pain (proportional odds ratio: 5.48, 95% confidence interval: 1.96, 15.3; p  = 0.001) compared with no flat feet, adjusted for age, sex, body mass index, and tibiofemoral joint K/L grade, which is consistent across various different cutoffs of the definition of flat feet. Physical performance was similar between patients with and without bilateral flat feet. The presence of unilateral flat feet was not significantly associated with any outcome measures. These findings indicate that bilateral, but not unilateral, flat feet are associated with worse knee pain. A prospective study investigating a causal relationship between bilateral flat feet posture and knee pain as well as disability would be of particular interest to verify the potential adverse effect of altered foot posture. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:2490–2498, 2017.